Trawler fuel exhaust and respiratory impairments: a cross-sectional pilot study among Indian fishermen working in informal sectors. (September 2015) - Moitra, Subhabrata; Maity, Santi Gopal; Haldar, Prasun; Pandit, Asis Kumar; Sahu, Subhashis
Abstract : Background: An estimated half a billion people are engaged in fishing related occupations in India. Exposure to adulterated fuel exhaust is common among deep-sea fishermen, yet little is known about the potential impacts on the exposure to health. Objective: The aim of this study was to investigate whether fuel emission exposure was associated with increased respiratory impairments among fishermen who were occupationally exposed to fuel exhaust compared to fisherman occupationally unexposed to fuel exhaust. Methods: This cross-sectional study compared the prevalence of respiratory symptoms and lung function variables between 152 marine-water and 107 fresh water fishermen considering the use of fuel-driven trawlers. Data were obtained from questionnaires and computerized spirometer. Results: Fishermen exposed to trawler fuel exhaust reported more than double the number of respiratory symptoms compared to the unexposed fisherman (86·2 vs. 40·2%). They also had a significantly higher chance experiencing chronic cough (adjusted OR = 3·51, 95% confidence interval (CI) = 2·09–6·35), chronic phlegm (8·61, 4·76–15·97), and wheezing (4·29, 2·55–7·61) symptoms. Finally, there was a significant reduction of the ratio of mid portion of forced expiratory flow rate and forced vital capacity (FEF25–75 /FVC) in the exposed fishermen compared to the unexposed (0·84 vs. 0·73 second −1, P  = 0·015). Conclusion: Fuel exhaust may negatively impact on the respiratory health of Indian fishermen. More attention and surveillance of occupational health for fishermen in India is needed.